Viral Infections in Neonates with Suspected Late-Onset Bacterial Sepsis—A Prospective Cohort Study - Kidszun, André; Klein, Lena; Winter, Julia; Schmeh, Isabella; Gröndahl, Britta; Gehring, Stephan; Knuf, Markus; Weise, Kerstin; Mildenberger, Eva (American Journal of Perinatology, 2017)
Objective The aim of our study was to evaluate the occurrence of viral infections in infants with suspected late-onset bacterial sepsis in a neonatal intensive care unit.Methods In a prospective study, infants with suspected late-onset bacterial sepsis underwent viral testing alongside routine blood culture sampling. Using a multiplex reverse transcription-polymerase chain reaction enzyme-linked immunosorbent assay, nasopharyngeal aspirates were analyzed for adenovirus, respiratory syncytial virus (RSV), influenza virus A and B, H1N1 virus, parainfluenza virus 1 to 4, metapneumovirus, coronavirus, and picornavirus. Stools were examined for adenovirus, rotavirus, norovirus, and enterovirus.Results Between August 2010 and March 2014, data of 88 infants with 137 episodes of suspected late-onset bacterial sepsis were analyzed. Six infants were diagnosed with a respiratory viral infection (2 × RSV, 4 × picornavirus). Blood culture–proven bacterial sepsis was detected in 15 infants. Neither viral–bacterial coinfections nor polymerase chain reaction positive stool samples were found.Conclusion Respiratory viruses can be detected in a considerable number of neonates with suspected late-onset bacterial sepsis. In contrast, gastrointestinal viral or enterovirus infections appear uncommon in such cases.
Keywords: virus; infection; late-onset bacterial sepsis; neonatal intensive care unit